Analisis Korporasi Petani Berbasis Kawsan Di Desa Trimoharjo Kabupaten OKU Timur - Harlina Safitri, Gita; Yamin, Muhammad; Bidarti, Agustina (AGRICA, 2024)
Farmer corporations are something new in Indonesia's agricultural development process. PT Sembada Agro Lestari is a concrete manifestation of the KSPP-based corporation program in the East Ogan Komering Ulu district. The purpose of establishing a corporation is to facilitate the farming activities of fostered farmers, from providing inputs, tools, and rice seeds, buying and selling crops to processing agricultural products. Farmer corporations play a role in increasing production and meeting food needs which will impact productivity, income of fostered farmers, and the welfare of farmers in East OKU District itself. This study aims to determine the effect of the corporate approach on the productivity, income and exchange rate by analyzing differences in productivity, income, and exchange rate of farmers in Trimoharjo Village, East Ogan Komering Ulu Regency. The method used in this research is the survey method with 105 sample farmers as respondents. For sample withdrawal use proportionate stratified random sampling method. The results showed that the productivity of layer I farmers was higher than layer II farmers with a productivity difference of 1.252 kg for rice commodity and 756.94 kg for corn commodity. Furthermore, the income of layer I farmers is higher than layer II farmers with a difference of Rp13,165,826.16. Meanwhile, the farmer exchange rate (NTP) of layer I farmers is greater than layer II farmers because some layer II farmers do not store grain so farmers need to buy rice for consumption, and many layer II farmers don’t plant corn.